Comparison of Dexmedetomidine and Fentanyl as Adjuvants to Intrathecal Isobaric Levobupivacaine in Lower Segment Caesarean Section - Rehman Zahid , Talha; Hinna, Rashk-e; Hayat, Arshad; Bashir, Rubina; Rauf Asghar, Arshman; Afzal, Muhammad (Scripta Medica, 2024)
Background/Aim: Caesarean section is one the most common surgeries encountered in the operating room worldwide in the younger demographic ages from 18-39 years of age. The objective of this study was to compare the efficacy of dexmedetomidine versus fentanyl as adjuvants to intrathecal levobupivacaine in the lower segment caesarean section. Methods: This quasi-experimental study was carried out at the Anaesthesia Department, Combined Military Hospital, Rawalpindi, Punjab, Pakistan from July 2021 to July 2023. A total of 240 patients were studied. They were divided into the dexmedetomidine group (n = 120) and fentanyl group (n = 120) group. Patients in both groups received 2.5 mL of 0.5 % of isobaric levobupivacaine with the dexmedetomidine group receiving 5 mcg of the drug and the fentanyl group 25 mcg of fentanyl to a total volume of 3 mL. Primary variables measured were: time to complete sensory and motor block, total duration of the block, time to first rescue analgesia after block regression in the post anaesthesia care unit (PACU) and mean PACU stay. Secondary variables observed were hypotension, nausea, vomiting and shivering. Results: The time on onset for a sensory block in the dexmedetomidine group was delayed compared to the fentanyl group (4.35 ± 0.14 min and 3.39 ± 0.11 min, respectively), (p < 0.0001). The duration of the block was longer for the dexmedetomidine group with a mean time of 327.26 ± 12.60 min versus 243.3 ± 22.75 min (p < 0.0001). When comparing the motor blockade, the time of onset to successfully reach Bromage score 3 was similarly delayed in the dexmedetomidine group with a mean time of onset of 3.33 ± 0.12 min versus 2.36 ± 0.09 min (p < 0.0001). A similar trend was seen in the duration of the block with a mean time of 262.17 ± 13.31 min versus 203.34 ± 1.47 min (p < 0.0001). Conclusion: Dexmedetomidine offered advantages over fentanyl as an adjunct to levobupivacaine spinal anaesthesia with a longer block duration and less adverse effects profile. It is recommended to use dexmedetomidine due to its better safety profile, longer duration and better hemodynamic stability. Fentanyl should be reserved when the early onset of the block is required in emergency cases.